«The last man of the nineteenth century»: A. Chekhov and Yu. Olesha - Борбунюк, Валентина Алексеевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In the article on the basis of Yu. Olesha`s publicism and diary notes the reception of creative heritage of A. Chekhov is traced. The reasons for the writer`s issuing to creativity of A. Chekhov are explained and the results of this interaction are detected. It is shown that Yu. Olesha perceived Chekhov’s creativity and personality of the writer as an opportunity to unite two epochs. Being a successor of the ideological and esthetic traditions of the XIX century, Yu. Olesha himself became an integral part of the culture of a new era, and his work – one of the events through which the past is due to the present with “the unbroken chain”.